Quantifying fire regimes and their impact on the Irish landscape - Hawthorne, Donna (Trinity College (Dublin, Ireland). Department of Botany, 2016)
This thesis examines the role of fire in the Irish landscape in the past, its drivers, impacts and interactions with the surrounding landscape, vegetation, climate and humans. Lacustrine sediment is utilised from seven study sites from a range of locations throughout Ireland, from upland, lowland and midland sites, to provide a multi-proxy record of charcoal and pollen. Four main research questions are addressed; 1. What was the nature and scale of fire in the Irish landscape in the past? -- 2. Are there common trends in fire that can be identified on a national and international scale? -- 3. How did this fire impact the surrounding landscape and vegetation? -- 4. Does fire have an impact on biodiversity and on what level?
Keywords: Botany, Ph.D.; PhD Trinity College Dublin, 2016